Superelastic damping at nanoscale in ternary and quaternary Cu-based shape memory alloys - Gómez Cortés, J.F. (2021)
Superelasticity is a characteristic thermomechanical property in shape memory alloys (SMA), which is due to a reversible stress-induced martensitic transformation. Nano-compression experiments made possible the study of this property in Cu–Al–Ni SMA micropillars, showing an outstanding ultra-high mechanical damping capacity reproducible for thousands of cycles and reliable over the years. This scenario motivated the present work, where a comparative study of the damping capacity on four copper-based SMA: Cu–Al–Ni, Cu–Al–Be, Cu–Al–Ni–Be and Cu–Al–Ni–Ga is approached. For this purpose, [001] oriented single-crystal micropillars of comparable dimensions (around 1 µm in diameter) were milled by focused ion beam technique. All micropillars were cycled up to two hundred superelastic cycles, exhibiting a remarkable reproducibility. The damping capacity was evaluated through the dimensionless loss factor η, calculated for each superelastic cycle, representing the dissipated energy per cycle and unit of volume. The calculated loss factor was averaged between three micro-pillars of each alloy, obtaining the following results: Cu–Al–Ni η = 0.20 ± 0.01; Cu–Al–Be η = 0.100 ± 0.006; Cu–Al–Ni–Be η = 0.072 ± 0.004 and Cu–Al–Ni–Ga η = 0.042 ± 0.002. These four alloys exhibit an intrinsic superelastic damping capacity and offer a wide loss factor band, which constitutes a reference for engineering, since this kind of micro/nano structures can potentially be integrated not only as sensors and actuators but also as dampers in the design of MEMS to improve their reliability. In addition, the study of the dependence of the superelastic loss factor on the diameter of the pillar was approached in the Cu–Al–Ni–Ga alloy, and here we demonstrate that there is a size effect on damping at the nanoscale.